Bank Capital Regulation and Endogenous Shadow Banking Crises - Johannes Poeschl; Xue Zhang (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We study the macroeconomic effects of bank capital requirements in an economy with two banking sectors. Banks are connected through a wholesale funding market. Anticipated banking crises occur endogenously in the form of self-fulfilling wholesale funding rollover crises. Retail bank capital requirements can reduce the frequency and severity of banking crises. Tightening retail bank capital requirements increases the size and leverage of the shadow banking sector through a novel channel that works through the anticipation of banking crises. A policy which corrects this spillover is more than twice as effective in reducing the frequency and severity of banking crises.
Keywords: E44; G24; G28; 330; Bank capital regulation; shadow banking; anticipated bank runs